Soft Frequency Reuse Based Spectrum Sharing Scheme in the Integrated Satellite and Terrestrial Network - Yang, Mingchuan; Xue, Guanchang; Xie, Bingyu; Dou, Yingzhe (Frontiers in Space Technologies, 2022)
The integrated satellite and terrestrial network has become one of the cutting-edge technologies of the next generation mobile communication system. The satellite network is used as an extension and supplement of the ground network to achieve seamless coverage of wireless mobile communications. The spectrum sharing of the integrated satellite and terrestrial network is realized from the perspective of spectrum planning, considering the number of co-frequency terminals and the distance between the terminal and the center of the satellite beam. The existing spectrum sharing schemes use the concept of geographic isolation, which will limit the available bandwidth of the terrestrial network. Therefore, the concept of time domain isolation is proposed, and a soft frequency reuse based spectrum sharing scheme in the integrated satellite and terrestrial network is designed. The allocation of time slots increases the degree of spectrum isolation and improves the signal to interference ratio of the network. In addition, due to the increase in the utilization rate of the satellite spectrum, the capacity of the satellite system is improved.